Coagulation/flocculation process with polyaluminum chloride for the remediation of oil sands process-affected water: Performance and mechanism study. (1st September 2015) - Wang, Chengjin; Alpatova, Alla; McPhedran, Kerry N.; Gamal El-Din, Mohamed
Abstract: This study investigated the application of polyaluminum chloride (PACl) for the treatment of the oil sands process-affected water (OSPW). These coagulants are commonly used in water treatment with the most effective species reported to be Al13 . PACl with 83.6% Al13 was synthesized using the slow base titration method and compared with a commercially available PACl in terms of aluminum species distribution, coagulation/flocculation (CF) performance, floc morphology, and contaminant removal. Both coagulants were effective in removing suspended solids, achieving over 96% turbidity removal at all applied coagulant doses (0.5–3.0 mM Al). The removal efficiencies of metals varied among different metals depending on their pKa values with metal cations having pKa values (Fe, Al, Ga, and Ti) below OSPW pH of 6.9–8.1 (dose dependent) being removed by more than 90%, while cations with higher pKa values (K, Na, Ca, Mg and Ni) had removals of less than 40%. Naphthenic acids were not removed due to their low molecular weights, negative charges, and hydrophilic characteristics at the OSPW pH. At the highest applied coagulant dose of 3.0 mM Al, the synthetic PACl reduced Vibrio fischeri inhibition effect to 43.3 ± 3.0% from 49.5 ± 0.4% in raw OSPW. In contrast, no reduction of toxicity was found for OSPW treated with the commercial PACl. Based on water quality and floc analyses, the dominant CF mechanism for particle removal during OSPW treatment was considered to be enmeshment in the precipitates (i.e., sweep flocculation). Overall, the CF using synthesized PACl can be a valuable pretreatment process for OSPW to create wastewater that is more easily treated by downstream processes. Graphical abstract: Highlights: Polyaluminum chloride products used for oil sands process-affected water treatment. Main mechanism for particle removal was enmeshment in precipitate. Dissolved organic matter was removed through adsorption. Removal efficiency of metal cations was correlated to their pKa values.